Capturing the productive use dividend: Valuing the synergies between rural electrification and smallholder agriculture in Ethiopia - Borgstein, Edward; Mekonnen, Dawit Kelemework; Wade, Kester; Anchala, Chimdo; Elisha, Francis; Eshetu, Yiheyis; Ernst, Kendall; Santana, Scarlett; Teshome, Kebede (Rocky Mountain Institute, 2020)
This report examines six agricultural production and processing opportunities for rural areas: horticulture irrigation, grain milling, injera baking, milk cooling, bread baking, and coffee washing. Collectively, these areas have the potential to produce US$4 billion in annual value using electric appliances by 2025. Supplying the appliances is itself a US$380 million investment opportunity. These six areas can also produce an additional US$22 million annual revenue stream for the utility by 2025, as the utility can sell more units of power with the same capital investment in rural areas. This revenue would help reduce the cost of providing power from both grid extension and minigrids. Realizing the economic and livelihood benefits of productive uses requires concerted national efforts linking agriculture and electrification. A national productive use program should address barriers and channel funding to the highest-need areas, helping to scale uptake rapidly. Immediate next steps are to study demand more closely, pilot several projects, and convene actors from different sectors to build a national vision and strategy